Combined oral contraceptives & cerebral venous sinus thrombosis: 2 cases and review - Singla, Anshuja; Yadav, Garima; Shree, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The incidence of venous thromboembolism with combined oral contraceptive is 20-30 per 1 lakh women years. Studies have shown that there is an increasing risk of VTE in current users and risk decreases with both time of use and decreasing estrogen dose. We report two cases in which both women had CVST triggered by combined oral contraceptive use. Before prescribing COCs, a complete personal and family history along with evaluation of risk factors for VTE and cardiovascular diseases is mandatory to ensure safe use of COCs.